2012
DOI: 10.3945/ajcn.111.022889
|View full text |Cite|
|
Sign up to set email alerts
|

Differential effects of polyphenols and alcohol of red wine on the expression of adhesion molecules and inflammatory cytokines related to atherosclerosis: a randomized clinical trial

Abstract: The results suggest that the phenolic content of RW may modulate leukocyte adhesion molecules, whereas both ethanol and polyphenols of RW may modulate soluble inflammatory mediators in high-risk patients. The trial was registered in the International Standard Randomized Controlled Trial Number Register at http://www.isrctn.org/ as ISRCTN88720134.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(102 citation statements)
references
References 47 publications
6
92
2
2
Order By: Relevance
“…Small randomised controlled clinical studies, however, as well as an observational study of 483 subjects followed for four years, suggest that moderate alcohol consumption reduces C-reactive protein, and the pro-inflammatory cytokines interleukin-6 and tissue necrosis factor-␣ [158,165,166]. Supporting the results of initial in vitro studies [167], a down-regulation and hence reduction in the plasma concentration of the soluble inflammatory mediators CD40 ligand, IL-16, monocyte chemotactic protein (MCP)-1, vascular cell adhesion molecule (VCAM)-1 and E-selectin has also been recently observed in high-CVD-risk subjects following 30 g of alcohol/day [168].…”
Section: Inflammatory Effectssupporting
confidence: 54%
“…Small randomised controlled clinical studies, however, as well as an observational study of 483 subjects followed for four years, suggest that moderate alcohol consumption reduces C-reactive protein, and the pro-inflammatory cytokines interleukin-6 and tissue necrosis factor-␣ [158,165,166]. Supporting the results of initial in vitro studies [167], a down-regulation and hence reduction in the plasma concentration of the soluble inflammatory mediators CD40 ligand, IL-16, monocyte chemotactic protein (MCP)-1, vascular cell adhesion molecule (VCAM)-1 and E-selectin has also been recently observed in high-CVD-risk subjects following 30 g of alcohol/day [168].…”
Section: Inflammatory Effectssupporting
confidence: 54%
“…Furthermore, red wine, which contains phenolic compounds, has been shown to affect the composition of human gut microbiota [37]. Phenolic compounds of red wine down-regulated serum concentrations of several cytokines and inflammatory markers, whereas others were increased [38]. Thus, the effect of ethanol in red wine may be counterbalanced by phenolic compounds.…”
Section: Patients With Irritable Bowel Syndromementioning
confidence: 99%
“…There is limited and conflicting evidence from interventional studies, typically with sample sizes of <100 participants and over relatively short periods of time, of the association between alcohol consumption and inflammation 7, 27, 28, 29. In terms of observational studies, some investigators have found that moderate alcohol consumption is associated with lower levels of CRP 30, 31, 32 and IL‐6 32, 33 compared to no alcohol and heavy alcohol intake, whereas others have observed no association 33, 34.…”
Section: Introductionmentioning
confidence: 99%